Modeling of Two-Motor Front-Wheel Drive Control for Electric Vehicle with Electronic Differential Based on Energetic Macroscopic Representation - Ihor Shchur; Ihor Havdo; Yurii Biletskyi (Energy Engineering and Control Systems)
Unlike a car, a modern electric vehicle (EV) can have different configurations of the electrical traction subsystem using one, two or four drive-wheel electric motors. This paper investigates a two-motor front-wheel drive configuration, in which the control of the electromagnetic torques of the motors provides two functions: electric traction and direction control. The latter function performs an electronic differential, which is used in place of the traditional mechanical differential transmission and mechanical steering system. The implementation of the aforementioned functions has been put on the developed motor drive control system based on Ackermann-Jeantaud geometry. For the study of the experimental EV, a new energy-based approach for constructing mathematical models of complex systems - Energetic Macroscopic Representation (EMR) is used. According to the inverse principle provided by EMR, EV motion control system was developed. Conducted simulation studies in the software Matlab/Simulink showed the efficiency of the developed control system and high accuracy of maintaining the set speed and direction of motion in both steady and transient modes of EV.